METHANE HYDRATE: KILLER CAUSE OF EARTH’S GREATEST MASS EXTINCTION - BRAND, Uwe; GRIESSHABER, Erika; ANGIOLINI, Lucia; AZMY, Karem; FARABEGOLI, Enzo; CAME, Rosemarie E.; POSENATO, Renato (2015)
The cause for the end Permian mass extinction, the greatest challenge life on Earth faced in its geologic history, although still hotly debated it bears an important message for humanity. The most significant marker of this event is the negative δ13C shift and rebound recorded in marine carbonates with a duration ranging from 2000 to 19,000 years. Leading cause for the event are Siberian trap volcanism and its emission of greenhouse gases with consequent global warming, but other leading contenders are oceanic anoxia and acidification. We present measurements of gases vaulted in shell calcite of end Permian brachiopods and whole rock, documenting significant differences in normal atmospheric equilibrium concentration (NAEC) of gases between modern and end Permian seawaters. The gas composition recorded in end Permian brachiopod gas-inclusions reflects dramatically higher seawater methane contents leading up to the event. Initial global warming of 8 to 11°C sourced by isotopically light carbon dioxide from volcanic emissions triggered the sudden release of methane from permafrost and shelf sediment hydrate. Consequently, the huge quantities of methane emitted into the atmosphere and the oceans accelerated global warming and marked the negative δ13C spike observed in marine carbonates marking the onset of the biggest mass extinction in Earth history. The rapidity of the methane emission lasting from several years to thousands of years was tempered by the equally rapid oxidation of the atmospheric and oceanic methane that gradually reduced its warming potential but not before global warming had reached levels lethal to most life on land and in the oceans. Based on measurements of gases trapped in biogenic and abiogenic calcite, the release of methane (of ~ 8 -28 % of total C stored) from permafrost and shelf sediment hydrate was the ultimate source and cause for the dramatic life-changing global warming (GMAT > 34°C) and oceanic (negative carbon isotope excursion) changes observed during the end Permian. Global ...